POTENSI SERAPAN KARBONDIOKSIDA (CO2) PADA POHON PENEDUH DI JALAN SOEKARNO HATTA KOTA PEKANBARU - Mhd. saputra pane; Defri Yoza; Rudianda Sulaeman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Global warming become a hot issue in recent years, a source and cause of global climate change is the amount of carbon dioxide emissions produced by fossil fuels used motor vehicles and some of the industry to run the engine. One solution that is appropriate in reducing carbon emissions is the availability of green open space around the road traffic. This research intend to discover the potential uptake of carbon dioxide and some plant species potentially absorb carbon dioxide in the shade trees at Soekarno Hatta Pekanbaru street. This research using purposive sampling method to determine the sample leaves on plants. The trees sampled is the most dominant tree on the green line at Soekarno Hatta Pekanbaru street. The tree used in this research as many as 27 trees, ie 9 angsana (Pterocarpus indicus Willd.), 9 mahogany (Swietenia macrophylla King.) and 9 eucalyptus (Melaleuca leucadendron L.). The results show angsana has potential of carbon dioxide absorption highest than mahogany and eucalyptus at Soekarno Hatta Pekanbaru street. Keywords: Carbondioxide, Angsana, Mahogany, and Eucalyptus.